Evaluation of User Acceptance of Online Transportation Applications Using User Acceptance Testing - Muhammad Arizal Dwisakti; Suci Ramadhani; Pristiwanto (Jurnal Armada Informatika, 2026)
This study evaluates user acceptance of online transportation applications using a questionnaire-based User Acceptance Testing (UAT) approach. The assessment covers vehicle ordering, location tracking, payment, navigation, processing speed, ease of use, comfort, and accessibility. Data were collected online from 30 active users through ten statements measured on a five-point Likert scale. Instrument validity was examined using the Pearson Product Moment correlation, while internal consistency was assessed using Cronbach’s Alpha. All items exceeded the critical correlation value of 0.361, with coefficients ranging from 0.4039 to 0.7380. The Alpha coefficient of 0.8148 indicated good instrument reliability. The observed score was 1,214 out of a maximum of 1,500, producing a UAT percentage of 80.93%. Under the interpretation interval adopted in this study, the application category was very feasible and reflected a high level of user acceptance. However, the result represents aggregated user perceptions and does not demonstrate that every function is technically error-free. The findings provide an initial evaluation, while future work should examine a specific application through controlled task scenarios, a larger sample, and item-level analysis.